Analyzing a group of EFL learners' productsOftwo dictations : Oreseeing orthographical difficulties and planning pronunciation exercises = Análisis del producto de dos dictados por parte de un grupo de estudiantes de inglés: anticipando dificultades ortográficas y planeandoejercicios de pronunciación - Navas Brenes, César Alberto 1976- (2014)
This article analyzes the phoneme-grapheme correspondence in the products of two orthographic-text dictations taken by a group of sixteen English majors at the School of Modern Languages at the University of Costa Rica. Accordingly, before administering the dictation of the first text, the author looks for a correlation between a list of foreseen spelling difficulties and the possible mistakes the students will eventually make while decoding and transcribing the troublesome words and phrases of the text. Once the spelling difficulties have been identified, the author presents a series of pronunciation activities to help learners raise awareness towards this spotted difficulty. After this group of students carries out these pronunciation activities, the author administers a second dictation to observe the improvement reached and the effect of formal instruction on the students' second dictation.
Este artículo analiza la correspondencia fonema-grafema en los productos de dos dictados llevados a cabo por un grupo de dieciséis estudiantes de la carrera de inglés de la Escuela de Lenguas Modernas en la Universidad de Costa Rica. De la misma manera, antes de administrar el dictado del primer texto, el autor busca una correlación entre una lista de dificultades ortográficas y los posibles errores que los y las estudiantes podrán eventualmente cometer al decodificar y transcribir las palabras y frases difíciles. Una vez identificadas las dificultades ortográficas, el autor presenta una serie de actividades de pronunciación con el fin de ayudar a los y las estudiantes a crear conciencia acerca de la dificultad previamente encontrada. Después de que este grupo de estudiantes lleva a cabo las actividades de pronunciación, el autor administra un segundo dictado para observar el mejoramiento alcanzado así como el efecto de la instrucción formal en el segundo dictado.
En Revista Intersedes, vol. 15, no. 32 (diciembre 2014)
Descripción basada en el contenido visto el 18 de diciembre, 2024